2014
DOI: 10.3171/2014.7.focus14344
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcomes after endoscopic management of cholesterol granulomas of the petrous apex: a systematic review

Abstract: Object Endoscopic endonasal treatment of petrous apex cholesterol granulomas allows for a natural drainage pathway into the nasopharynx. Because of the limited number of case series in the literature, there is limited evidence of recurrence rates and outcomes following endoscopic endonasal management. The purpose of this study was to determine the surgical outcomes of endoscopic endonasal approaches in the treatment of cholesterol granulomas of the petrous apex. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 37 publications
1
35
1
Order By: Relevance
“…When compared to transtemporal approaches, the aggregate evidence to date suggests excellent outcomes with regard to symptomatic improvement with the endoscopic approach. In a systematic review of 53 patients, Eytan et al . reported that only 7.5% experienced recurrent symptoms.…”
Section: Benign Lesionsmentioning
confidence: 99%
“…When compared to transtemporal approaches, the aggregate evidence to date suggests excellent outcomes with regard to symptomatic improvement with the endoscopic approach. In a systematic review of 53 patients, Eytan et al . reported that only 7.5% experienced recurrent symptoms.…”
Section: Benign Lesionsmentioning
confidence: 99%
“…The use of silastic stent would be effective in prevention of recurrence, but its removal would need additional surgery under local anesthesia, or general anesthesia in some cases [10]. Moreover, the 13 of 14 (92.9%) reported cases of PACG treated by pedicle flap without stent did not present with recurrence [12,14,22], suggesting non-inferiority of the pedicle flap technique compared with the use of silastic stent. Although the combined use of pedicle flap and stent was also recommended [11], we consider the use of pedicle flap without stent as an optimum and less invasive procedure for PACG.…”
Section: Discussionmentioning
confidence: 99%
“…Before the advent of endoscopic surgery, the recurrence rate following microscopic TSS for PACG was quite high [27]. In recent years, however, the recurrence rate of endoscopic TSS has extremely reduced [10,12,16,22]. Compared with microscopy, endoscopy can achieve a wide operative field, enabling a maximum puncture of CG.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations